Rivastigmine for ECT-induced cognitive adverse effects in late life depression (RECALL study): A multicenter, randomized, double blind, placebo-controlled, cross-over trial in patients with depression aged 55 years or older: Rationale, objectives and methods - Henstra, Marieke J.; Feenstra, Thomas C.; Kok, Rob M.; Spaans, Harm-Pieter; van Exel, Eric; Dols, Annemiek; Oudega, Mardien; Vergouwen, Anton C. M.; van der Loo, Adriano; Bet, Pierre M.; Loer, Stephan A.; Eikelenboom, Merijn; et al. (Frontiers in Psychiatry, 2022)
Background: Cognitive side-effects are an important reason for the limited use of electroconvulsive therapy (ECT). Cognitive side-effects are heterogeneous and occur frequently in older persons. To date, insight into these side-effects is hampered due to inconsistencies in study designs and small sample sizes. Among all cognitive side-effects, confusion and delirious states are especially troublesome for patients, relatives and clinicians. In particular inter-ictal delirium-like states are worrisome, since it may lead to premature treatment discontinuation. Besides a need for further insight into determinants of cognitive side-effects of ECT, there is a great need for treatment options. Methods and design: The Rivastigmine for ECT-induced Cognitive Adverse effects in Late Life depression (RECALL) study combines a multicenter, prospective cohort study on older patients with depression, treated with ECT, with an embedded randomized, placebo-controlled cross-over trial to examine the effect of rivastigmine on inter-ictal delirium. Patients are recruited in four centers across the Netherlands and Belgium. We aim to include 150 patients into the cohort study, in order to be able to subsequently include 30 patients into the trial. Patients are included in the trial when inter-ictal delirium, assessed by the Confusion Assessment method (CAM), or a drop in Mini Mental State Examination (MMSE) score of ≥4 during ECT, develops. In the cohort study, comprehensive measurements of ECT-related cognitive side-effects – and their putative determinants – are done at baseline and during the ECT-course. The primary outcome of the clinical trial is the effectiveness of rivastigmine on inter-ictal delirium-severity, assessed with a change in the Delirium Rating Scale-Revised-98. Secondary outcomes of the clinical trial are several ECT-characteristics and side-effects of rivastigmine. Discussion: This study is the first clinical trial with a focus on ECT-induced, inter-ictal delirium. The cohort provides the basis for recruitment of patients for the cross-over trial and additionally provides an excellent opportunity to unravel cognitive side-effects of ECT and identify putative determinants. This paper describes the rationale and study protocol. Clinical trial registration: EudraCT 2014-003385-24